A Comparison of Nationalized and Private Banks' Strategic Human Resource Management Practices - JAINH, DR MANJULA (The journal of contemporary issues in business and government, 2021)
The analysis of banking is as interesting because of its size and scope as ever. Development steady. Liberalization, fiscal and technical changes Modernization has pushed the banking industry to become competitive. The need for competitive people has been created by competition. Each bank has begun to take Decisions on human capital concerning their competing banks. It gave birth to the implementation of strategic control of human capital, where human resources are Strategies are formulated with the opponent in mind. The bank has become more of a bank today. The objective of the study is to make a comparison of Nationalized and Private Banks' Strategic Human Resource Management Practices. Conclusions drawn are generalizations reached by bearing in mind the goal and goals of the analysis from the outcomes that are related to hypotheses. The results and assumptions are focused on the primary and secondary interpretation of knowledge. An effort is made to shed light on the way and extent of execution of the plan by description and results. Suggestions are made based on these observations and assumptions to analyze banks for their previous success and conditions for potential improvement. Specific attempts are being made to achieve the goals of this study and to open up a new basis for future research and further studies in this field.